2013
DOI: 10.1007/s10571-013-9972-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of MTHFR C677T Gene Polymorphism, Biochemical and Clinical Parameters in Turkish Migraine Patients: Association with Allodynia and Fatigue

Abstract: We investigated whether there is any relationship between biochemical and clinical parameters of migraine and methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphism, associated with the migraine subtypes, symptoms, and gender. A total of 150 migraine patients with and without aura (MA and MO) and 107 non-sufferers were included in the study. Biochemical and clinical parameters were measured and genetic analysis was performed. The MTFHR C677T genotype was significantly higher in the migraine group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…29 patients out of 56 had migraine with aura and 27 had migraine without aura. Several studies have shown a significantly higher frequency for migraine without aura, which makes up ~70% of all migraine cases [6] [17] [37]. These findings were not in accordance with our findings in the Estonian pediatric migraine population; the frequency of both subtypes was almost the same.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…29 patients out of 56 had migraine with aura and 27 had migraine without aura. Several studies have shown a significantly higher frequency for migraine without aura, which makes up ~70% of all migraine cases [6] [17] [37]. These findings were not in accordance with our findings in the Estonian pediatric migraine population; the frequency of both subtypes was almost the same.…”
Section: Discussioncontrasting
confidence: 99%
“…This disorder is classified in two subtypes: migraine with aura (MA) and without aura (MO) [5]. MA comprises nearly 25% of all migraine cases in overall migraine population [6]. It is described by a disturbance of motor and visual activities that lasts 20 to 30 minutes before the migraine attack [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were published from 2003 to 2015, including six case-control studies (Bahadir et al, 2013; Helbig et al, 2003; McLaren et al, 2008; Piraino et al, 2012; Utge et al, 2010), five cohort studies (Allen et al, 2008; Bull et al, 2009; Lotrich et al, 2010; Scotet et al, 2005; Udina et al, 2013), three cross-sectional studies (Maluchenko et al, 2009; Ragnarsson et al, 2014; Vazquez-Rey et al, 2005), two longitudinal studies (Lee et al, 2014; Sundstrom et al, 2007) and two clinical trials (Becker et al, 2015; van der Deure et al, 2008). Sample sizes ranged from 33 to 31,192.…”
Section: Resultsmentioning
confidence: 99%
“…The genes under investigations from these studies can be grouped into 3 categories: neurotransmitter systems and HPA axis (five studies) (Bahadir et al, 2013; Bull et al, 2009; Maluchenko et al, 2009; Ragnarsson et al, 2014; Utge et al, 2010), inflammation (six studies) (Becker et al, 2015; Helbig et al, 2003; Lee et al, 2014; Lotrich et al, 2010; Piraino et al, 2012; Udina et al, 2013) and other mechanisms (seven studies) (Allen et al, 2008; Dlugos et al, 2010; McLaren et al, 2008; Scotet et al, 2005; Sundstrom et al, 2007; van der Deure et al, 2008; Vazquez-Rey et al, 2005). …”
Section: Resultsmentioning
confidence: 99%